2018
DOI: 10.1126/scirobotics.aat5843
|View full text |Cite
|
Sign up to set email alerts
|

Not as bad as it seems: When the presence of a threatening humanoid robot improves human performance

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 18 publications
4
46
3
3
Order By: Relevance
“…According to the Ethopoeia concept [10], automatic social reactions are triggered by situations that include social cues, which need not all originate from other humans [11], [12]. This concept also seems to apply to human-robot interactions (HRIs) [3], [5], [7], [10], [13]. For example, it has been shown that the modalities of interaction might directly affect how humans consider artificial social agents in response to the same robot [3], [5], [6].…”
Section: Month 2019 • Ieee Robotics and Automation Magazine •mentioning
confidence: 99%
See 4 more Smart Citations
“…According to the Ethopoeia concept [10], automatic social reactions are triggered by situations that include social cues, which need not all originate from other humans [11], [12]. This concept also seems to apply to human-robot interactions (HRIs) [3], [5], [7], [10], [13]. For example, it has been shown that the modalities of interaction might directly affect how humans consider artificial social agents in response to the same robot [3], [5], [6].…”
Section: Month 2019 • Ieee Robotics and Automation Magazine •mentioning
confidence: 99%
“…This concept also seems to apply to human-robot interactions (HRIs) [3], [5], [7], [10], [13]. For example, it has been shown that the modalities of interaction might directly affect how humans consider artificial social agents in response to the same robot [3], [5], [6].…”
Section: Month 2019 • Ieee Robotics and Automation Magazine •mentioning
confidence: 99%
See 3 more Smart Citations